Analisis dan Perbaikan Proses Bisnis Menggunakan Metode Business Process Improvement (BPI) (Studi Kasus : Bidang Usaha Perikanan Lele di PT. MaksiPlus Utama Indonesia) - Fandika Rakhman Nanda; Herman Tolle; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
MaksiPlus Utama Indonesia is a distribution company that engaged in fisheries, agriculture, and animal husbandry in Indonesia. The fisheries sector at PT. MaksiPlus Utama Indonesia named Lelenesia has four business processes, including supply, product processing, product sales, and product ordering. While running its business, Lelenesia does not yet have clear and standard business process documentation. There are still obstacles such as the business process carried out in Lelenesia not according to the specified time target. This happened because there were obstacles that hindered the running of business activities in Lelenesia. The expectation of Lelenesia owners is to consider the use and assistance of information systems, business processes can run more efficiently in the future. Based on the problems that have been described, an analysis and improvement is made on the ongoing business processes. The analytical method used is the Business Process Improvement (BPI) conducted from phase 1: Organizing for improvement to phase 3: Streamlining. After get the results of the analysis and evaluation, the next step is to do simulation of business process. The simulation results show that there is a reduction in the total time in the business process that has been repaired, namely, the supply supply process is 169 minutes, the product sales process is 12,846 minutes, and the product ordering process is 1,700 minutes. So it can be concluded that the time needed to run the recommendation business process is more efficient than the current business process in the Catfish Fisheries Business Sector PT. MaksiPlus Utama Indonesia.